IMPACT OF SOCIAL MEDIA ON SPIRITUAL TOURISM IN PROMOTING ECONOMIC DEVELOPMENT OF TEMPLES FROM THE INDIAN CONTEXT - Dr. P. MANIKANDAN; Mrs. KARISHMA CHAUHAN (The Bioscan, 2025)
This investigation study intends to do a fact check on the effect of communal mass media on spiritual tourism and its association with the growth of the Indian economy, which will offer development to the concern & other temples. Further studies also aim to look at the factors of facts and pattern analysis of spiritual tourists. The sample size has been determined as 374, and a convenience sampling method was deployed to gather primary data. The methods adopted for analysis include simple percentage analysis, regression, analysis of variance, standard deviation, average and mean, and relative importance index for impact ranking. Further, the outcomes of the analysis have been interpreted to provide meaningful insights. It is recently evident from the Maha Kumbh 2025 festival, that it is a rare occurrence that has a massive movement of devotees across all states of India and abroad. It has contributed both expenses and revenues to the government. Small vendors and businessmen have used this opportunity to increase their sales and services to earn more profit. Pertaining to each temple across the nation has its unique features and purpose; they have been exhibited to the people through the effective reach of Communal broadcasting. Interested devotees seek attention over such temples and fund them during their visit; further, due to their visit, nearby businesses and vendors are benefitted. Therefore, the transport facilities and amenities inside & outside the temples shall be facilitated by the state government once they see the increase in devotees with due respect to the revenue generated towards it. The outcomes of this research also revealed that there is a direct and strong influence that exists, which is created by Communal broadcasting as the impact that will help the economic development of temples and the nation. However, the results were limited to the region of the study; they might vary from time, place, and other factors, etc.